Rapid Outgassing of Hydrophilic TiO2 Electrodes Achieves Long-Term Stability of Anion Exchange Membrane Water Electrolyzers - Shajahan Shaik; Jeonghyeon Kim; Mrinal Kanti Kabiraz; Faraz Aziz; Joon Yong Park; Bhargavi Rani Anne; Mengfan Li; Hongwen Huang; Ki Min Nam; Daeseong Jo; Sang-Il Choi (Nano-Micro Letters)
Highlights A super-hydrophilic electrode was successfully developed by depositing porous NiFe nanoparticles onto annealed TiO2 nanotubes (NiFe/ATNT), facilitating rapid outgassing of nonpolar gases. The NiFe/ATNT electrode demonstrated an overpotential of 235 mV at 10 mA cm−2 for the oxygen evolution reaction in 1.0 M KOH and served as the anode in the anion exchange membrane water electrolyzer (AEMWE), achieving a current density of 1.67 A cm−2 at 1.80 V. The AEMWE utilizing the NiFe/ATNT electrode exhibited remarkable stability, maintaining operation for 1500 h at 0.50 A cm−2 under challenging thermal conditions of 80 ± 3 °C.